2016
DOI: 10.1038/npp.2016.267
|View full text |Cite
|
Sign up to set email alerts
|

Methylphenidate Enhances Early-Stage Sensory Processing and Rodent Performance of a Visual Signal Detection Task

Abstract: Methylphenidate (MPH) is used clinically to treat attention-deficit/hyperactivity disorder (ADHD) and off-label as a performance-enhancing agent in healthy individuals. MPH enhances catecholamine transmission via blockade of norepinephrine (NE) and dopamine (DA) reuptake transporters. However, it is not clear how this action affects neural circuits performing cognitive and sensorimotor functions driving performance enhancement. The dorsal lateral geniculate nucleus (dLGN) is the primary thalamic relay for visu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
20
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(22 citation statements)
references
References 47 publications
1
20
1
Order By: Relevance
“…We conclude that lowering of glutamatergic excitability increases the use of resting periods, reduces distraction by concurrent environmental stimuli, reduces unnecessary exploratory behavior in favor or goal-directed behavior and allows for better selective attention and better performance in tasks requiring high attention and fast responses to visual light/ LED stimuli. The behavior of LPAR2 −/− mice has some similarity with mouse behavior under methylphenidate in models addressing attention or sensory processing [47][48][49]. Notably, glutamate overflow leads to attentional deficits [50] and the 5CSRT touchscreen task has indeed some predictive validity for selecting drugs effective for treating attentiondeficit/hyperactivity disorder [51].…”
Section: Discussionmentioning
confidence: 99%
“…We conclude that lowering of glutamatergic excitability increases the use of resting periods, reduces distraction by concurrent environmental stimuli, reduces unnecessary exploratory behavior in favor or goal-directed behavior and allows for better selective attention and better performance in tasks requiring high attention and fast responses to visual light/ LED stimuli. The behavior of LPAR2 −/− mice has some similarity with mouse behavior under methylphenidate in models addressing attention or sensory processing [47][48][49]. Notably, glutamate overflow leads to attentional deficits [50] and the 5CSRT touchscreen task has indeed some predictive validity for selecting drugs effective for treating attentiondeficit/hyperactivity disorder [51].…”
Section: Discussionmentioning
confidence: 99%
“…Beyond that, certain levels of NE contribute to the detection of environmental stimuli by priming sensory neurons. Application of pharmacological agents promoting the cortical NE supply provided evidence for facilitated processing of visual stimuli in primary sensory neurons (Borodovitsyna, Flamini, & Chandler, 2017;Navarra et al, 2017;Zitnik, Clark, & Waterhouse, 2014). Experiments with auditory signals (Manunta & Edeline, 2004) and those activating the gustatory sense (Heath et al, 2006) also demonstrated that NE increased the neuronal sensitivity for relevant information in the domain-specific cortical target regions.…”
Section: The Locus Coeruleus-norepinephrine System and Cognitionmentioning
confidence: 98%
“…Therefore, in addition to promoting waking, NE at particular levels might facilitate detection of sensory stimuli by priming sensory neurons. For example, LC stimulation and drugs that promote noradrenergic transmission have both been shown to increase responsiveness to visual stimulation in primary sensory neurons in the lateral geniculate nucleus [ 9 , 10 , 63 , 64 ]. Through these combined actions, NE may have procognitive effects simply by rendering animals more alert and more sensitive to salient sensory stimuli in their environments.…”
Section: Role Of Norepinephrine In Prefrontal Cortical and Hippocamentioning
confidence: 99%